Application of Mann-Kendal (MK) test in trend analysis of air temperature and precipitation: Case of Mačva district (Serbia) - Milentijević Nikola; Bačević Nikola; Ristić Dušan; Valjarević Aleksandar; Pantelić Milana; Kićović Dušan (The University Thought: Publication in Natural Sciences, 2020)
Recent climate changes cause significant natural and socio-economic consequences. They represent one of the major environmental problems of the late 20th and early 21st centuries. Changes in temperature and precipitation play a significant role in understanding climate change issues. They include numerous extreme climatic events such as heat waves, droughts, forest fires and more. Looking at regional differences in temperature and precipitation regime change, Southern Europe, including the Republic of Serbia, occupies a special place. The Mačva district (3.272 km²) is almost four times as spacious as the Mačva area. The administrative-political division of the Mačva district is comprised of eight municipalities. The paper presents trends of two climate variables: mean annual air temperature and mean annual precipitation in the study area. In methodological sense, the main statistical procedure is the non-parametric Mann-Kendall (MK) test. Data from three available meteorological stations in the Mačva district (1949-2015) were used for the analysis. The presented results of the trends in air temperature indicate that there is a statistically significant positive trend in all-time series. In trends, precipitation amounts a statistically significant positive trend was observed in two time series, while in one there is no trend. The expressed trends, especially in the case of air temperatures, lead to the possibility of drought. Mačva district and Mačva have some agricultural importance in the Republic of Serbia. For these reasons, some adaptation to climate change is needed as arid conditions lead to fluctuations in agricultural yield.